(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
The growing phenomenon of “rooftopping”, unauthorized climbing of tall buildings publicized through social media, raises new legal questions, particularly regarding the qualification of criminal acts and criminal liability for unauthorized entry into restricted areas. The marriage proposal staged atop the antenna of the Empire State Building, New York, on 1 July 2026 illustrates how an act perceived as romantic can carry serious criminal consequences under United States law. This article examines the regulation of unauthorized entry into restricted areas under United States law and compares it with Indonesian law to identify similarities, differences, and implications should a similar act occur within Indonesian jurisdiction. This research employs a normative juridical method using statutory, case, comparative, and conceptual approaches. The findings show that United States law, through New York Penal Law Article 140, regulates trespassing and burglary in a tiered manner based on location, means, and time of the act, with penalties ranging from violations to serious felonies. In contrast, Indonesian law, both under Article 167 of the old Criminal Code and Article 257 of the new Criminal Code (Law Number 1 of 2023), regulates such conduct in a single article with comparatively lighter penalties and a narrower “forcible entry” element compared to the broader “knowingly entering without right” element under United States law. This structural difference implies a potential legal gap should a similar event occur in Indonesia, particularly concerning the still-unregulated phenomenon of high-rise building climbing stunts.